An Introduction to the Impact of Knowledge Management in Lean Manufacturing: Based on the impact of knowledge flows - He, Xingsong (International Journal of Global Economics and Management, 2024)
With the advent of the knowledge economy, knowledge has become a very important resource and one of the core competencies of an organization. However, the current lean manufacturing implementation process in most companies focuses on the sequence of the production process without paying attention to the process of integrating relevant knowledge in the organization. This paper explores the application of knowledge management in the lean manufacturing implementation process, especially the impact of the key attribute of knowledge flow in the improvement process of lean manufacturing. Therefore, both knowledge management and data analysis have a very important role to play in the implementation of lean manufacturing in an organization. Enterprises need to continuously explore and practice and optimize lean production methods and techniques to improve their competitiveness and core value.